Legal Determinants of Health: Regulating Abortion Care. (29th June 2020) - McGuinness, Sheelagh; Montgomery, Jonathan
Abstract: In The legal determinants of health: Harnessing the power of law for global health and sustainable development, Gostin et al. provide a sustained account of how law can and should be used as an instrument of health promotion. We pick up on the themes of this report with a specific focus of the importance of abortion for women's sexual and reproductive health and the impact that particular ways of framing abortion in law can have on the lives of women and girls. In this short comment, we wish to emphasize that abortion regulations need to move beyond frameworks based on narrow understandings of harm towards more progressive agendas that take into account the social determinants of health in order to reduce barriers to care. This contribution is particularly relevant to the Commission's criticism that those '[l]aws that stigmatise or discriminate against marginalized populations are especially harmful and exacerbate health disparities'.